PENGARUH NON PERFOMING LOAN (NPL) TERHADAP RETURN ON ASSET (ROA) PADA BANK MANDIRI,TBK - SUPRATMAN, IMAM; MUNIARTY, PUJI; NURULRAHMATIA, NAFISAH (Universitas Mahasaraswati K. Mataram, 2024)
This research aims to find out the influence of Non-Performing Loans (NPL) on ROA at Bank Mandiri. Correlational quantitative research is the research method used. Financial reports, profit and loss statements, balance sheets and cash flow reports for the years 2013–2022 are the research samples. For this particular case, purposive sampling was used. The relationship between the NPL variable and ROA was tested using simple linear regression, correlation coefficient, coefficient of determination, and two-square t-test. Analysis was carried out using SPSS v.22 software. In line with the high level of non-performing loans faced by banks. This is because the higher NPL level indicates that banks are not managing their credit optimally and are not providing adequate protection to their customers. As a result, the absence of principal and interest payments on credit facilities causes the bank's return on assets to decline along with the increase in the non-performing loan ratio